2018
DOI: 10.21873/anticanres.12230
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Pancreatic Metastases from Renal Cell Carcinoma in Patients Treated with Tyrosine Kinase Inhibitors

Abstract: Abstract. Aim: The study aimed to define the true impact of pancreatic metastases (PM) from renal cell carcinoma on overall survival (OS) in patients treated with first-line tyrosine kinase inhibitors. Patients and Methods: Overall, 321 consecutive patients were analysed. The influence of PM on OS was assessed using the Kaplan-Meier estimator and the logrank test (unadjusted and adjusted) and two multivariabe Cox proportional hazards regressions (CPHR =0.84, p=0.603, and HR=0.66, p=0.098). Conclusion: The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…It has even been proposed that pancreatic location of metastases is characteristic for RCC tumors with a less aggressive phenotype. We have previously shown that the presence of pancreatic metastases was not an independent prognostic factor in multivariate analysis, but it was an indicator of an indolent course of the disease in the general RCC population 42 .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…It has even been proposed that pancreatic location of metastases is characteristic for RCC tumors with a less aggressive phenotype. We have previously shown that the presence of pancreatic metastases was not an independent prognostic factor in multivariate analysis, but it was an indicator of an indolent course of the disease in the general RCC population 42 .…”
Section: Discussionmentioning
confidence: 89%
“…In contrast to patients with liver metastases, patients with pancreatic metastases are known to have indolent disease and longer median OS. Reported median OS for patients with pancreatic metastases is 39–46.1 months, while for patients without pancreatic metastases it is 23.1–26 months, but with all other secondary tumor locations 4042 . It has even been proposed that pancreatic location of metastases is characteristic for RCC tumors with a less aggressive phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…This example illustrates that by closely monitoring blood glucose and providing extra trypsin after total pancreatectomy, the patient could have a better quality of life. In addition to the widely used prognostic factor model from the Memorial Sloan Kettering Cancer Center [ 31 33 ], vascular invasion [ 2 ], presence of symptoms [ 34 ], and tumor size more than 3 cm [ 35 ] may be associated with an increased risk of death. However, the localization and number of metastatic lesions have no effect on the site of metastases [ 34 ], which is in line with our current results.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, the literature review confirms that clinical prognostic factors that reflect tumour burden and tumour growth rate, such as size, occurrence of multiple metastases, DFI, or synchronous occurrence of PM, which are generally relevant in metastasis surgery of solid carcinomas [136][137][138], remain ineffective with isPMRCC. In particular, the complete lack of influence of the tumour volume on survival contradicts a general concept of cancer, in which a greater tumour burden of the body results in a poorer outcome [139].…”
Section: Ispmrcc and The Impact Of Prognostic Factors On Osmentioning
confidence: 97%